Genetic diversity and infection sources of Rosellinia necatrix in northern Israel - DAFNY-YELIN, Mery; MAIRESSE, Orly; MOY, Jehudith; DOR, Shlomit; MALKINSON, Dan (Phytopathologia Mediterranea, 2018)
Symptoms of white root rot (caused by Rosellinia necatrix) of fruit trees (including apple, cherry and peach) are rotting of the roots and yellowing of the leaves, followed by wilting and death. Undecomposed organic material in forest soils is favourable for growth of R. necatrix. Genetic tools and mycelial compatibility assays can be used to group the fungus into genetically similar groups. This study identified and located the sources of root infection, using broad surveys of infested plots in various locations, and assessed infection probability as a function of distance from potential inoculum source. Fifty-five infested plots in 14 settlements at different altitudes were surveyed. About 60% of the infested plots, at altitudes up to 540 m above sea level, were located near Mediterranean oak maquis forests, and the infections spread inward from the edges of the fruit orchards. These results indicated four possible sources of infection: (i) Mediterranean maquis forest near agricultural lands; (ii) soil transferred to low-lying sections within orchards; (iii) infection source carried by farmers from plots on the same farm; and (iv) infections via roots of adjacent trees within orchards. No correlation was found between genetic variation and virulence, but isolates that grew quickly on potato dextrose agar plates at 28oC were more virulent than slow growing isolates.